2003
DOI: 10.1017/s0031182003003743
|View full text |Cite
|
Sign up to set email alerts
|

Fish macroparasites as indicators of heavy metal pollution in river sites in Austria

Abstract: This paper describes two approaches to evaluate the use of fish macroparasites as bioindicators of heavy metal pollution at selected river stretches in Austria. Firstly changes in the diversity and richness of endoparasites of the cyprinid barbel, Barbrus barbuls (L.), were tested in relation to heavy metal contents in the aquatic system. Secondly, the bioaccumulation potential of cadmium, lead and zinc was assessed in the acanthocephalan, Pomphorhynchus laevis (Miller, 1776), and compared with that in the mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 30 publications
7
51
0
Order By: Relevance
“…The expected mercury biomagnification has not always been involved because the parasite may not be regarded as a trophic equivalent of predators (Bergey et al, 2002). The present study also revealed that R. paranensis did not reduce the accumulation of mercury in its fish host as observed by other authors (Sures, 2001(Sures, , 2003(Sures, , 2004Bergey et al, 2002;Sures et al, 2003;Schludermann et al, 2003;Thielen et al, 2004;Tekin-Ozan & Kir, 2005). For example, when exposed to methylmercury in the laboratory, the grass shrimp Palaemonetes pugio, infested by the isopod Probopyrus pandalicola, accumulated lower concentrations of mercury than their non-infested counterparts (Bergey et al, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The expected mercury biomagnification has not always been involved because the parasite may not be regarded as a trophic equivalent of predators (Bergey et al, 2002). The present study also revealed that R. paranensis did not reduce the accumulation of mercury in its fish host as observed by other authors (Sures, 2001(Sures, , 2003(Sures, , 2004Bergey et al, 2002;Sures et al, 2003;Schludermann et al, 2003;Thielen et al, 2004;Tekin-Ozan & Kir, 2005). For example, when exposed to methylmercury in the laboratory, the grass shrimp Palaemonetes pugio, infested by the isopod Probopyrus pandalicola, accumulated lower concentrations of mercury than their non-infested counterparts (Bergey et al, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…Certain fish parasites, particularly intestinal acanthocephalans and cestodes, are widespread and common fish parasites, and they can accumulate heavy metals at concentrations significantly higher than those in host tissues or the environment (Sures, 2001(Sures, , 2003(Sures, , 2004Sures et al, 2003;Schludermann et al, 2003;Thielen et al, 2004;Tekin-Ozan & Kir, 2005). These parasites have been indicated as tools for monitoring of heavy metal pollution by Cd, Cu, Pb, and Zn, among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, parasitic infections are known to cause massive mortality in the fry and fingerling stages, especially in high-density aquaculture systems [23] [24]. In the present study, the high infection rate (65%) of C. gariepinus from Lake Manzala could therefore, be attributed to the contamination of the Lake by various pollutants and numerous tributaries coming from the River Nile.…”
Section: Discussionmentioning
confidence: 56%
“…This type of approach is very common in countries such as Germany and Austria, where Scheef et al [4,5] concluded that fish parasites are excellent environmental bioindicators due to their ability to accumulate larger amounts of trace elements. A proposal in this sense is necessary in order to understand the dynamics of the parasitofauna and to evaluate the quality of the aquatic ecosystem through the intestinal parasites.…”
Section: Introductionmentioning
confidence: 99%